Transformation of Islamic Education In The 5.0 Era: The Role of Quality Management in Improving the Standards and Relevance of Islamic Education - Asykur, Muamar; Ifriani, Ifriani; Hamriani, Selvi; S, Siti Munawira; Selfina, Selfina (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
The rapid development of technology in the Industrial Revolution 5.0 era has significantly changed various aspects of life, including the education sector. In the midst of the flow of globalization and digitalization in this era, Islamic education is required to maintain Islamic values, while increasing its relevance and quality standards in order to be able to compete globally.The transformation of Islamic education in the 5.0 Era requires a strategic approach to integrate technology with strengthening the principles of quality management in Islamic Educational Institutions. Where, quality management acts as a systematic framework to improve the performance of Islamic Educational Institutions by ensuring that Islamic education not only meets academic standards, but is also socially and spiritually relevant.Technology in the 5.0 era brings many benefits to Islamic Education.Adaptation of technology in Islamic education includes the use of educational software, e-learning platforms, social media, and other digital tools that aim to enrich students' learning experiences.However, in its utilization, the use of technology cannot be separated from negative impacts that need to be anticipated.